Strategi Pengolahan Bahan Pustaka sebagai Pusat Sumber Referensi Informasi di Perpustakaan Al-Kindi Madrasah Tsanawiyah (MTs) Negeri 2 Bandar Lampung - Rahmat Iqbal; Okta Reni Azrina RA; Aghesna Rahmatika Kesuma; Jeni Susana (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The school library is an important facility and infrastructure that is presented by a madrasa or school and has a collection of library materials whose information can help the community in the madrasa environment, including teachers, students, staff or guardians of students in obtaining the information needed. The activity of processing library materials is the spearhead in the creation of a library as a central source of reference for information and library materials. This is what underlies the need for a strategy in processing library materials, because library materials are the most important product in the library. The researcher used a qualitative descriptive method which was strengthened by literature review, interviews and observations. The strategy for processing library materials at Al-Kindi MTs Negeri 2 Bandar Lampung includes determining the classification number and subject of library materials, library automation, preservation of library materials, and colored labeling.